International Effect: The Ongoing Tension with Medical Marijuana Legalization - Vadasz , Gabriel (International Journal of Law and Policy, 2024)
Purpose: In the landscape of the United States, an escalating number of states are ushering in a new era by enacting legislation that affords individuals the right to employ cannabis for medical purposes. However, this commendable stride toward medical autonomy is accompanied by an escalating tension, a discordant symphony of conflict between state and federal jurisdictions. This study embarks on a journey through the labyrinth of legislative intricacies, seeking to unravel the roots of this tension and proffering insights into potential resolutions. At the heart of the matter lies the dichotomy between state and federal legislation. While states pave the way for medical cannabis use, the federal stance casts a looming shadow of ambiguity and discord. The conflict, multifaceted and dynamic, beckons for a nuanced exploration. Methodology: The study adopted desktop literature research design. Findings: By delving into the intricacies of the legislative measures themselves, this research identifies mitigating factors that can potentially alleviate the tension between conflicting jurisdictions. Mitigation, however, requires more than a superficial understanding of legislative nuances. It demands a comprehensive acknowledgment of the extensive legal and medical data interwoven with the fabric of cannabis use for medical purposes. Unique Contribution to Theory, Practice and Policy: The study advocates for a holistic approach, urging policymakers to draw upon a repository of knowledge that transcends mere legal frameworks. In doing so, it seeks to bridge the gap between state and federal perspectives, fostering a more informed and cooperative discourse. Navigating the path toward resolution involves a delicate balance. The sculpting of legislative measures should be informed by a deep appreciation of the medical intricacies associated with cannabis use. The study underscores the significance of considering medical data as an essential compass in the journey toward harmonizing state and federal regulations. By acknowledging the complex interplay between legality and medical efficacy, this research contributes to the ongoing dialogue surrounding cannabis legislation. In conclusion, this study illuminates the intricate dance between state and federal jurisdictions in the realm of medical cannabis use. Through a meticulous examination of legislative intricacies and a robust consideration of legal and medical data, it endeavors to pave the way for a more harmonious coexistence between state and federal perspectives.